Stunting, risk factor, effect and prevention - Setiyabudi, Ragil (MEDISAINS, 2019)
Stunting still becomes a problem for Indonesian today. There are many risk factors which cause stunting, whether in short and long term effect. It can be overcome by a national nutrition awareness movement which involves multiple sectors which addresses to pregnant/childbirth women, toddlers, school-age children, teenagers and young adults and family empowerment.